Low back pain as an equivalent of neurogenic claudication in elderly patient: Case report - Igor Borshchenko; Roman Kartavykh; Andrey Baskov; Andrey Grin; Maria Borshchenko (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2020)
This clinical report presents the case of chronic low back pain in elderly female referring to multilevel (L2-L5) degenerative lumbar spinal stenosis without typical neurogenic claudication and leg pain. Subsequent minimally invasive surgical decompression produced complete resolve of the pain and drastic improvement life quality. This surgery confirmed the pain origin and proves the possibility of sole low back pain as an equivalent of neurogenic claudication. Considering this type of clinical pattern of spinal stenosis can direct general practitioner or other medical professional to correct diagnosis and prompt surgical treatment.